2013
DOI: 10.1890/12-1497.1
|View full text |Cite
|
Sign up to set email alerts
|

Diel phosphorus variation and the stoichiometry of ecosystem metabolism in a large spring‐fed river

Abstract: Abstract. Elemental cycles are coupled directly and indirectly to ecosystem metabolism at multiple time scales. Understanding coupling in lotic ecosystems has recently advanced through simultaneous high-frequency measurements of multiple solutes. Using hourly in situ measurements of soluble reactive phosphorus (SRP), specific conductance (SpC), and dissolved oxygen (DO), we estimated phosphorus (P) retention pathways and dynamics in a large (discharge, Q ' 7.5 m 3 /s) spring-fed river (Ichetucknee River, Flori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
107
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(115 citation statements)
references
References 102 publications
7
107
1
Order By: Relevance
“…Collection of nutrient data at frequent intervals in aquatic systems has in almost all cases revealed much higher temporal variability than was evident in less frequent discrete sample collection (Bende-Michl et al 2013;Pellerin et al 2009Pellerin et al , 2011Pellerin et al , 2014Wild-Allen and Rayner 2014). These data also revealed patterns in nutrient dynamics that occur at yearly, seasonal, diurnal, tidal, and individual-event time-scales, which are difficult if not impossible to detect using lowerresolution data (Bende-Michl et al 2013;Bowes et al 2009;Cohen et al 2012Cohen et al , 2013Pellerin et al 2009Pellerin et al , 2011Pellerin et al , 2014Wild-Allen and Rayner 2014).…”
Section: Continuous Sensing Of Nutrients Within the Delta New Developmentioning
confidence: 98%
See 2 more Smart Citations
“…Collection of nutrient data at frequent intervals in aquatic systems has in almost all cases revealed much higher temporal variability than was evident in less frequent discrete sample collection (Bende-Michl et al 2013;Pellerin et al 2009Pellerin et al , 2011Pellerin et al , 2014Wild-Allen and Rayner 2014). These data also revealed patterns in nutrient dynamics that occur at yearly, seasonal, diurnal, tidal, and individual-event time-scales, which are difficult if not impossible to detect using lowerresolution data (Bende-Michl et al 2013;Bowes et al 2009;Cohen et al 2012Cohen et al , 2013Pellerin et al 2009Pellerin et al , 2011Pellerin et al , 2014Wild-Allen and Rayner 2014).…”
Section: Continuous Sensing Of Nutrients Within the Delta New Developmentioning
confidence: 98%
“…Although most high-frequency nutrient studies to date involve nitrate sensors, adoption of commercially available in situ analyzers for phosphate and prototype sensors for ammonium is growing (Rozemeijer et al 2010;Cassidy and Jordan 2011;Bende-Michl et al 2013;Cohen et al 2013;Gilbert et al 2013;Outram et al 2014;Bowes et al 2015). We are aware of few studies that report results from in situ high-frequency ammonium analyzers, and-not surprisingly-these studies found that ammonium, nitrate, and phosphate variability are not necessarily linked (Bende-Michl et al 2013;Gilbert et al 2013).…”
Section: Additional Nutrient Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Advances in data collection using continuously monitoring sensors deployed on buoys or other stationary structures for water monitoring will allow researchers to circumvent some of the previous limitations of sampling large rivers and increase the temporal resolution of measurements (Cohen et al 2013). NEON is collaborating with the US Army Corps of Engineers in placing sensors at the Alabama River sites near USGS gauging stations for real-time discharge monitoring.…”
Section: Large River Ecologymentioning
confidence: 99%
“…These factors make it difficult to link life-history traits with alterations in hydrologic variables without high-frequency measurements (Puckridge et al 1998). Cohen et al (2013) required very high temporal resolution of river data (on the scale of minutes) to distinguish between biotic and abiotic mechanisms of nutrient retention in a Florida river, suggesting that NEON's continuous monitoring on the Black Warrior-Tombigbee River system is a strong approach for documenting the influence of multiple variables on ecosystem processes.…”
Section: Large River Ecologymentioning
confidence: 99%